Retkulocyte production index in various anemia - Setyawati Setyawati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2005)
Background: Reticulocyte production index (IPR) is used to determine the classification of functional anemia. More specific laboratory parameters are used in managing patient. There were some inappropriate of IPR correlation with the diagnosis of anemia in clinical practice.Objectives: The study was designed to know normal hematocrit in Sardjito General Hospital, to determine IPR in various anemia and to compare with standard IPR and final diagnosis in anemia. Methods: Observational study was done in patients with anemia who whole blood examination in uderwent Clinical Pathology Laboratory on January 2001 until May 2002. Reticulocyte and hematocrit examination were performed before treatment. Patients were followed until. The diagnosis of anemia was established based on the clinical manifestations and laboratory results. Normal mean calculated hematocrit was based on age and sex. IPR was calculated based on standard hematocrit (45%) and mean normal hema-tocrit.Results: The normal mean hematocrit in male, female, children and infant were 43%, 39%, 40% and 48%, respectively. There was significant difference between the 2 formulas. The concordance of IPR determination in hipoproliferative anemia and maturation defects were 100%, in hemolytic/hemorrhagic anemia and maturation defect was 23,5%. The IPR of hypoproliferative anemia and maturation defect anemia differed significantly with haemolytic/ hemorrhagic anemia. IPR determination using factual hematpcrit show a better correlation with classification of functional than using standard hematocrit of 45%.Conclusion: IPR determination based on normal calculated hematocrit mean gave more benefit in increasing the correlation with classification of functional anemia. IPR value showed inappropriate result in hemolytic/hemorhagic anemia probably due to comorbidities.Key words: IPR - functional clasification anemial - anemia - normal calculated hematocrit